2020
DOI: 10.1117/1.jbo.25.6.066003
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow energy photoacoustic microscopy for ocular imaging in vivo

Abstract: Significance: The development of ultralow energy photoacoustic microscopy (PAM) on the clinically relevant pigmented rabbit eye model paves a road toward translation of the emerging PAM technology in ophthalmology clinics. Aim: Since the eye is particularly vulnerable to laser damage, we aim to develop an ultralow energy PAM system to significantly improve the laser safety of PAM by increasing the sensitivity of the system and reducing the incident laser energy for imaging. Approach: A multichannel data acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…PAM serves as a safe imaging modality because it does not produce ionizing radiation, and the energy levels emitted from the laser diode can be significantly below American National Standards Institute (ANSI) laser safety limits. Recent studies by Li et al and Zhang et al performed a comprehensive safety evaluation of a PAM imaging system used to visualize retinal blood vessels and showed that pulsed-laser energy levels at 1.6 nJ (1 % of the ANSI safety limit) were able to generate defined images of the retinal vasculature without damage as per histological analysis [ 88 , 89 ], demonstrating that ultralow energy PAM systems can likely be applied safely in the future in clinical eye settings. In addition to uses in ophthalmology, PAM can be used for a variety of imaging applications, including oncology [ 90 , 91 ], neurology [ 92 , 93 ], dermatology [ 94 ], and gastroenterology [ 95 ].…”
Section: Advanced Ophthalmic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…PAM serves as a safe imaging modality because it does not produce ionizing radiation, and the energy levels emitted from the laser diode can be significantly below American National Standards Institute (ANSI) laser safety limits. Recent studies by Li et al and Zhang et al performed a comprehensive safety evaluation of a PAM imaging system used to visualize retinal blood vessels and showed that pulsed-laser energy levels at 1.6 nJ (1 % of the ANSI safety limit) were able to generate defined images of the retinal vasculature without damage as per histological analysis [ 88 , 89 ], demonstrating that ultralow energy PAM systems can likely be applied safely in the future in clinical eye settings. In addition to uses in ophthalmology, PAM can be used for a variety of imaging applications, including oncology [ 90 , 91 ], neurology [ 92 , 93 ], dermatology [ 94 ], and gastroenterology [ 95 ].…”
Section: Advanced Ophthalmic Imagingmentioning
confidence: 99%
“…While still a new and ongoing development, PAM imaging shows promise as an ophthalmic modality capable of safely producing images of high resolution and penetrance for the diagnosis and tracking of a variety of eye conditions. Multiple animal studies have shown excellent PAM imaging outcomes [ 88 , 96-98 ]. For example, in a study evaluating the progression of choroidal vascular occlusion (CVO), PAM imaging was able to successfully visualize CVO at high resolution over the course of 28 days [ 82 ].…”
Section: Advanced Ophthalmic Imagingmentioning
confidence: 99%
“…The laser light is then raster scanned point by point, within the field-of-view (FOV) of the transducer onto the target to be imaged [19]. LS-PAM has been implemented vigorously by many research groups working in the field of dermatology [20], oncology [21], neurology [22], and ophthalmology [23]. However, LS-PAM has a disadvantage of low signal-to-noise ratio (SNR) compared to traditional PAM configurations [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Photoacoustic microscopy (PAM) is a potential brain imaging modality, benefitting from the advantages of rich functional information in biological tissue. [1][2][3][4][5][6][7][8][9][10] PAM is based on the photoacoustic (PA) effect. Short laser pulse illuminates the biological tissues.…”
Section: Introductionmentioning
confidence: 99%